Enhancement of Electricity Production by Graphene Oxide in Soil Microbial Fuel Cells and Plant Microbial Fuel Cells - Goto, Yuko; Yoshida, Naoko; Umeyama, Yuto; Yamada, Takeshi; Tero, Ryugo; Hiraishi, Akira (Frontiers in Bioengineering and Biotechnology, 2015)
The effects of graphene oxide (GO) on electricity generation in soil microbial fuel cells (SMFCs) and plant microbial fuel cell (PMFCs) were investigated. GO at concentrations ranging from 0 to 1.9 g•kg-1 was added to soil and reduced for 10 days under anaerobic incubation. All SMFCs (GO-SMFCs) utilizing the soils incubated with GO produced electricity at a greater rate and in higher quantities than the SMFCs which did not contain GO. In fed-batch operations, the overall average electricity generation in GO-SMFCs containing 1.0 g•kg-1 of GO was 40 ± 19 mW•m-2, which was significantly higher than the value of 6.6 ± 8.9 mW•m-2 generated from GO-free SMFCs (p < 0.05). The increase in catalytic current at the oxidative potential was observed by cyclic voltammetry (CV) for GO-SMFC, with the CV curve suggesting the enhancement of electron transfer from oxidation of organic substances in the soil by the reduced form of GO. The GO-containing PMFC also displayed a greater generation of electricity compared to the PMFC with no added GO, with GO-PMFC producing 49 mW•m-2 of electricity after 27 days of operation. Collectively, this study demonstrates that GO added to soil can be microbially reduced in soil, and facilitates electron transfer to the anode in both SMFCs and PMFCs.